Effect of Proximal Row Carpectomy and Wrist Arthrodesis on the Resting Length of Extrinsic Digit Flexor Tendons: A Cadaveric Study - Carrazana-Suárez, Luis F.; Rivera, Lenny; Olivella, Gerardo; Natal-Albelo, Eduardo; Portalatín, Edwin; Deliz-Jiménez, David; Bibiloni-Lugo, José P.; Torres-Lugo, Norberto J.; Ramírez, Norman; Foy-Parrilla, Christian (Journal of Hand and Microsurgery, 2022)
Background Spastic joint contractures remain a complex and challenging condition. For patients with upper extremity spastic dysfunction, improving the muscle balance is essential to maximize their hand function. Multiple procedures, including proximal row carpectomy (PRC) and wrist arthrodesis (WA), are considered among the different surgical alternatives. However, the biomechanical consequences of these two procedures have not been well described in current literature. Hence, the objective of our study is to assess the change in the extrinsic digit flexor tendon resting length after proximal row carpectomy and wrist arthrodesis.Methods Six fresh-frozen cadaver upper extremities (four females and two males) with no obvious deformity underwent dissection, PRC, and WA. All the flexor digitorum profundus (FDP), flexor digitorum superficialis (FDS), and flexor pollicis longus (FPL) tendons were marked proximally 1-cm distal to their respective myotendinous junction and cut distally at the marked point. The overlapping segment of each distal flexor tendon from its proximal mark was considered the amount of flexor tendon resting length change after PRC and WA. A descriptive evaluation was performed to assess the increment in tendon resting length. Additionally, a regression analysis was performed to evaluate the relation between the tendon resting length and the proximal carpal row height.Results Following PRC and WA, the mean digit flexor tendon resting length increment achieved across all tendons was 1.88 cm (standard deviation [SD] = 0.45; range: 1.00–3.00 cm). A weak direct relationship (R = 0.0334) between the increment in tendon resting length and proximal carpal row height was initially suggested, although no statistical significance was demonstrated (p = 0.811).Conclusion This study provides an anatomic description of the increased extrinsic digit flexor tendon resting length after PRC and WA in cadaveric specimens. Findings provide a useful framework to estimate the amount of extrinsic digit flexor resting length increment achieved after wrist fusion and the proximal carpal row removal.
Keywords: proximal row carpectomy; flexor tendon resting length; wrist arthrodesis; proximal carpal row height; cadaveric study